Adaptability of winter rye cultivars by yield in the conditions of the Kirov region - E. S. Parfenova; E. A. Psareva (Аграрная наука Евро-Северо-Востока, 2024)
The breeding of winter rye for adaptability is an important factor in increasing yield and stabilizing gross grain yields.  The research was conducted in 2018–2023 in the central agroclimatic zone of the Kirov region. Thirteen cultivars of winter rye (Secale cereale L. var. vulgare Koern.) of the mid-late maturity group of different breeding periods (‘Falenskaya 4’ as standard) were studied in the nursery of competitive variety testing. Based on the “yield” trait, the parameters of the general adaptive ability of the cultivar (GAAi), stability (σ2SAAi), breeding value of the genotype, and responsiveness of the genotype to changes in environmental conditions (bi) were determined using the method of A. V. Kilchevsky and L. V. Khotyleva. The "year" factor had the greatest influence on the “yield” trait (the influence of factor hx2 = 60 %). With high winter hardiness (4.7 points) and plant regeneration (89 %), the yield of winter rye is associated with the amount of precipitation during the resumption of vegetation in April (r = -0.92), as well as during the period “seedlings-autumn tillering” and the “earing” phase (r = 0.55). According to the yield, the ‘Grafinya’ (5.09 t/ha) and ‘Lika’ (5.07 t/ha) cultivars were distinguished with a significant increase to the standard of 0.40 t/ha and 0.38 t/ha, respectively (LSD05 = 0.24 t/ha). The ‘Grafinya’, ‘Lika’, ‘Batist’, and ‘Perepel’ cultivars had a high general adaptive ability (GAAi = 0.23–0.51). Cultivars of late breeding periods were characterized by a higher general adaptive ability (GAAi = 0.09–0.51) compared to previously created cultivars (GAAi = -0.61…0.01). The cultivars ‘Vyatka 2’,’Kiprez’, ‘Kirovskaya 89’, ‘Sadko’, ‘Grafinya’, ‘Batist’, ‘Rushnik’, ‘Perepel’ were distinguished by high stability of the "yield" trait (σ2SAA = 0.50–0.73). The lowest stability indicators were found in the cultivars ‘Flora’, ‘Lika’, ‘Talitsa’ (σ2SAA = 1.13–1.35). The cultivars ‘Flora’, ‘Lika’, ‘Talitsa’, ‘Falenskaya 4’, ‘Perepel’, ‘Rushnik’ were highly responsive to improving growing conditions (bi = 1.1–1.4). The cultivar ‘Grafinya’ combined high yield and stability (selection value of the genotype 2.9).